Preferring balanced vs. advantageous peace agreements: A study of Israeli attitudes towards a two state solution - Deepak Malhotra; Jeremy Ginges (Judgment and Decision Making, 2010)
The paper extends research on fixed-pie perceptions by suggesting that disputants may prefer proposals that are perceived to be equally attractive to both parties (i.e., balanced) rather than one-sided, because balanced agreements are seen as more likely to be successfully implemented. We test our predictions using data on Israeli support for the Geneva Accords, an agreement for a two state solution negotiated by unofficial delegations of Israel and the Palestinian Authority in 2003. The results demonstrate that Israelis are more likely to support agreements that are seen favorably by other Israelis, but --- contrary to fixed-pie predictions --- Israeli support for the accords does not diminish simply because a majority of Palestinians favors (rather than opposes) the accords. We show that implementation concerns create a demand among Israelis for balance in the degree to which each side favors (or opposes) the agreement. The effect of balance is noteworthy in that it creates considerable support for proposals even when a majority of Israelis and Palestinians OPPOSE the deal.